Beckman PF-31 Ultrasonic Spirometer with unidentified accessory
Spirometers determine lung capacity and health by measuring how quickly respiration happens and how much air is both inhaled and exhaled.
Keywords: Medical electronics--Equipment and supplies; Spirometry--Equipment and supplies; Respiration--Measurement; Beckman Instruments, Inc.